Virtual Screening on Marine Natural Products for Discovering TMPRSS2 Inhibitors - Mahmudpour, Mehdi; Nabipour, Iraj; Keshavarz, Mohsen; Farrokhnia, Maryam (Frontiers in Chemistry, 2021)
Although SARS-CoV-2 entry to cells strictly depends on angiotensin-converting enzyme 2 (ACE2), this virus also needs transmembrane serine protease 2 (TMPRSS2) for its spike protein priming. It has been shown that the entrance of SARS-CoV-2 through ACE2 can be blocked by cellular TMPRSS2 blockers. The main aim of this study was to find potential inhibitor(s) of TMPRSS2 through virtual screening against a homology model of TMPRSS2 using the library of marine natural products (MNPs).The homology modelling technique for generating three-dimensional structure of TMPRSS2 was applied. Molecular docking, MM-GBSA and absorption, distribution, metabolism, excretion (ADME) evaluations were performed to investigate the inhibitory activity of Marine Natural Products (MNPs) against TMPRSS2 and their pharmacokinetic properties. Camostat and Nafamostat mesylate were used as the standard inhibitory molecules. Seven MNPs were able to inhibit TMPRSS2 better than the standard compounds. MNP 10 with CAS number 107503-09-3, called Watasenia β-D- Preluciferyl glucopyrasoiuronic acid was found to be the best inhibitor of TMPRSS2 with acceptable pharmacokinetic properties. Herein, for the first time, a new marine natural product was introduced with potent inhibitory effects against TMPRSS2. The MNP 10 exhibited a favorable drug-like pharmacokinetic properties and it promises a novel TMPRSS2 blocker in order to combat SARS-CoV-2.